2014
DOI: 10.18632/oncotarget.2296
|View full text |Cite
|
Sign up to set email alerts
|

Targeting RNA transcription and translation in ovarian cancer cells with pharmacological inhibitor CDKI-73

Abstract: Dysregulation of cellular transcription and translation is a fundamental hallmark of cancer. As CDK9 and Mnks play pivotal roles in the regulation of RNA transcription and protein synthesis, respectively, they are important targets for drug development. We herein report the cellular mechanism of a novel CDK9 inhibitor CDKI-73 in an ovarian cancer cell line (A2780). We also used shRNA-mediated CDK9 knockdown to investigate the importance of CDK9 in the maintenance of A2780 cells. This study revealed that CDKI-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 55 publications
3
36
0
Order By: Relevance
“…In this study, we present our findings on the CDK inhibitor LS-007 in acute leukemia both alone and in combination with ABT-199. LS-007 has been reported to be one of the most efficient CDK9 inhibitors and is effective in both CLL and ovarian tumors [19,20] . We evaluated the inhibitory activity of LS-007 against various CDKs and 41 types of non-CDK kinases at the molecular level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we present our findings on the CDK inhibitor LS-007 in acute leukemia both alone and in combination with ABT-199. LS-007 has been reported to be one of the most efficient CDK9 inhibitors and is effective in both CLL and ovarian tumors [19,20] . We evaluated the inhibitory activity of LS-007 against various CDKs and 41 types of non-CDK kinases at the molecular level.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that LS-007 had little toxicity on normal T-and B-cells while exhibiting potent efficiency alone or in combination with fludarabine against chronic lymphocytic leukemia (CLL) primary cells [19] . In addition, LS-007 exerted a potent antitumor effect in ovarian cancer A2780 cell lines through simultaneously targeting CDK9 and its downstream Mnk-eIF4E pathways [20] . These results provided convincing evidence that LS-007 may be a promising anti-tumor candidate deserving further development.…”
Section: Original Articlementioning
confidence: 99%
“…As CDK9 is involved in phosphorylating AR and RNAPII, evidences are accumulating supporting the re-establishment of transcriptional regulation via CDK9 inhibitors, not only in PCa, but in many other types of cancers. Inhibition of CDK9 expression using shRNA, triggered apoptosis of chronic lymphocytic leukemia cell and ovarian cancer, further supporting CDK9 as a potential anticancer therapeutic target (Lam et al 2014. There have been many efforts to develop CDK9 inhibitors and as a result several compounds have been shown to possess promising antitumor activities via inhibition of CDK9 in many human cancer models in vitro as well as in vivo (Table 3).…”
Section: Development Of Pharmacological Inhibitors Of Cdk9 For Pcamentioning
confidence: 97%
“…Inhibition of Mnk results in down-regulation of cell cycle regulatory proteins including cyclin D causing G 1 cell arrest [3,51e53]. In our recent study, CDK9 inhibition led to the downregulation of Mnk and the consequent reduction of eIF4E phosphorylation in ovarian cancer cells [32]. To ensure that the biological effects observed are exerted through Mnk inhibition and are not consequences of inhibiting CDK2 and CDK9, the assessment against both CDKs was also carried out for the initial selectivity profile.…”
Section: Assessment Of Mnk2 Inhibitorsmentioning
confidence: 99%